Small-aperture intraocular lens implantation in a patient with cataract and keratoconus. Issue 2 (24th April 2020) - Ezzeldin, Mona; Steinberg, Johannes; Frings, Andreas; Linke, Stephan
Abstract : A case of small-aperture intraocular lens (IOL) implantation in a patient with nuclear cataract and keratoconus is presented. The patient had femtosecond laser–assisted cataract surgery (FLACS) with implantation of a small-aperture lens into the right eye. Two weeks later, the left eye had FLACS with implantation of an aspheric lens inducing zero spherical aberrations. A small aperture IOL was implanted in the right eye due to the irregular cornea and an aspheric nontoric, monofocal IOL with an asphericity of zero was implanted in the left eye.